Metagenomic Analysis Indicates Epsilonproteobacteria as a Potential Cause of Microbial Corrosion in Pipelines Injected with Bisulfite - An, Dongshan; Dong, Xiaoli; An, Annie; Park, Hyung S.; Strous, Marc; Voordouw, Gerrit (Frontiers in Microbiology, 2016)
Sodium bisulfite (SBS) is used as an oxygen scavenger to decrease corrosion in pipelines transporting brackish subsurface water used in the production of bitumen by steam-assisted gravity drainage. Sequencing 16S rRNA gene amplicons has indicated that SBS addition increased the fraction of the sulfate-reducing bacteria (SRB) Desulfomicrobium, as well as of Desulfocapsa, which can also grow by disproportionating sulfite into sulfide, sulfur and sulfate. SRB use cathodic H2, formed by reduction of aqueous protons at the iron surface, or use low potential electrons from iron and aqueous protons directly for sulfate reduction. In order to reveal the effects of SBS treatment in more detail, metagenomic analysis was performed with pipe-associated solids (PAS) scraped from a pipe section upstream (PAS-616P) and downstream (PAS-821TP) of the SBS injection point. A major SBS-induced change in microbial community composition and in affiliated hynL genes for the large subunit of [NiFe] hydrogenase was the appearance of sulfur-metabolizing Epsilonproteobacteria of the genera Sulfuricurvum and Sulfurovum. These are chemolithotrophs, which oxidize sulfide or sulfur with O2 or reduce sulfur with H2. Because O2 was absent, this class likely catalyzed reduction of sulfur (S0) originating from the metabolism of bisulfite with cathodic H2 (or low potential electrons and aqueous protons) originating from the corrosion of steel (Fe0). Overall this accelerates reaction of of S0 and Fe0 to form FeS, making this class a potentially powerful contributor to microbial corrosion. The PAS-821TP metagenome also had increased fractions of Deltaproteobacteria including the SRB Desulfomicrobium and Desulfocapsa. Altogether, SBS increased the fraction of hydrogen-utilizing Delta- and Epsilonproteobacteria in brackish-water-transporting pipelines, potentially stimulating anaerobic pipeline corrosion if dosed in excess of the intended oxygen scavenger function.